Mobilizing Networks and Relationships Through Indigenous Food Sovereignty: The Indigenous Food Circle’s Response to the COVID-19 Pandemic in Northwestern Ontario - Levkoe, Charles Z.; McLaughlin, Jessica; Strutt, Courtney (Frontiers in Communication, 2021)
This paper explores the Indigenous Food Circle’s (IFC) response to the COVID-19 pandemic in Northwestern Ontario, Canada. Established in 2016, the IFC is an informal collaborative network of Indigenous-led and Indigenous-serving organizations that aims to support and develop the capacity of Indigenous Peoples to collaboratively address challenges and opportunities facing food systems and to ensure that food-related programming and policy meets the needs of the all communities. Its primary goals are to reduce Indigenous food insecurity, increase food self-determination, and establish meaningful relationships with the settler population through food. This community case study introduces the IFC and shares the strategies and initiatives that were used during the COVID-19 pandemic in 2020 to address immediate needs and maintain a broader focus on Indigenous food sovereignty. The food related impacts of the COVID-19 pandemic on Indigenous People and determining solutions cannot be understood in isolation from settler colonialism and the capitalist food system. Reflecting on the scholarly literature and the experiential learnings that emerged from these efforts, we argue that meaningful and impacting initiatives that aim to address Indigenous food insecurity during an emergency situation must be rooted in a decolonizing framework that centres meaningful relationships and Indigenous leadership.